Prolonged Resuscitation with Multiple Defibrillations; a Case Report - Rahmani, Shaghayegh; Mokhtari Amirmajdi, Elham; Kolahi Ahari, Rana; Farzaneh, Roohie (Archives of Academic Emergency Medicine, 2022)
Although American Heart Association Guidelines (AHA) are practical and standardized in many aspects of cardiopulmonary resuscitation (CPR) performance, recommendations on when to terminate resuscitation are not fully understood and clear. There is not enough evidence about how long we can continue CPR in shockable rhythms and how many shocks can be delivered to patients, and if there is an end point for it or not. This issue is more challenging when we read papers published on survival rates and good functional and neurological outcomes after prolonged CPRs. Here, we demonstrate a case of cardiac arrest receiving CPR in the emergency room, for whom it was hard and challenging to make a decision on when to terminate the resuscitation attempts.